(untitled) (Altre Modernità, 2015)
The essay "Going beyond the Window: the deconstructed Window" provides a critical interpretation of Zäzilie in Palmstrom (Humoristic Poems, III, 1990:128), one of the humoristic poems by C. Morgenstern. The essay makes an important reference to W. Ross, Zäzilie(II) (in Ein Knie geht einsam durch die Welt, 1989:108–111). In such a context, it first focuses on the concept of anti-bourgeois in Morgenstern’s poetics and interprets the reduction of the window to its wooden skeleton as a challenge posed by the man to the role of the objects in bourgeois aesthetics: the deconstructed window turns into the metaphor of an anti-mimetic view of the world. Second, the essay examines Zäzilie within the philosophical side of Morgenstern’s poetics: the “philosophical dilettantism” (Giffei, 1931:28). Finally, it provides an analysis of Zäzilie based on the main concepts of Morgenstern’s poetics. Such an analysis highlights that Zäzilie’s housework reproduces the author’s never-ending philosophical research and his way of looking “beyond and though” the man (Morgenstern, Letters, 1979:138).